2019
DOI: 10.1002/jum.15082
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Features and Treatment Options for Breast Pseudoaneurysms After Biopsy: A Case‐Based Pictorial Review

Abstract: Pseudoaneurysm (PSA) formation is a potential complication of breast biopsies. Ultrasound is the most common imaging modality used for evaluation and treatment of a PSA. Color Doppler images show a cystic structure with swirling flow inside in a "to-and-fro" pattern. Treatment options for PSA include observation, ultrasound-guided focused compression, thrombin injection, open surgical repair, and percutaneous embolization. The risks and benefits of these treatment options will be discussed in the following cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Open surgery is to be considered a last resource in case of the failure of the other methods [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Open surgery is to be considered a last resource in case of the failure of the other methods [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, several reports have demonstrated that treatment options of PA include US-guided focused compression, thrombin or ethanol injection, percutaneous intervention, and open surgical repair. [ 2 , 8 ] More detailed advantages and disadvantages of each treatment option were summarized in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Color Doppler ultrasound must be employed to confirm the diagnosis. Blood flow is characterized by a typical swirling motion, called the “Yin-Yang sign” [9] , [10] , [11] .…”
Section: Discussionmentioning
confidence: 99%